Gambaran Histopatologi Paru Mencit (Mus musculus) Setelah Pemaparan Paraquat - Aulia Wiradi; Wiwit Ade Fidiawati; Sri Melati Munir (Fakultas Kedokteran Universitas Riau, 2017)
Paraquat destroys organs including lung. Purpose of this study was to determine the effect of paraquat on histopathologyof lung, exspecially fibrosis in mice (Mus musculus). This study was an experimental study with post-test only withcontrol design and using 15 mice as sample. Samples were divided into 5 groups consist of one control group and fourdifferent doses of paraquat treatment group (25 mg / kg / day, 50 mg / kg / day, 75 mg / kg / day and 100 mg / kg / day for7 days with spraying). Analysis of the data have used One-Way ANOVA then post-hoc test with tukey to assesseddifferences of each groups. The results showed increasing of lung fibrosis with increasing doses and have significantcorrelations (p = 0.000). In conclusion, there are significant changes in lung histopathology of mice (Mus musculus)after paraquat exposure for 7 days.